FTO genotype and weight loss: systematic review and meta-analysis of 9563 individual participant data from eight randomised controlled trials. (20th September 2016) - Livingstone, Katherine M; Celis-Morales, Carlos; Papandonatos, George D; Erar, Bahar; Florez, Jose C; Jablonski, Kathleen A; Razquin, Cristina; Marti, Amelia; Heianza, Yoriko; Huang, Tao; Sacks, Frank M; Svendstrup, Mathilde; et al.
Abstract : Objective  To assess the effect of the FTO genotype on weight loss after dietary, physical activity, or drug based interventions in randomised controlled trials. Design  Systematic review and random effects meta-analysis of individual participant data from randomised controlled trials. Data sources  Ovid Medline, Scopus, Embase, and Cochrane from inception to November 2015. Eligibility criteria for study selection  Randomised controlled trials in overweight or obese adults reporting reduction in body mass index, body weight, or waist circumference by FTO genotype (rs9939609 or a proxy) after dietary, physical activity, or drug based interventions. Gene by treatment interaction models were fitted to individual participant data from all studies included in this review, using allele dose coding for genetic effects and a common set of covariates. Study level interactions were combined using random effect models. Metaregression and subgroup analysis were used to assess sources of study heterogeneity. Results  We identified eight eligible randomised controlled trials for the systematic review and meta-analysis (n=9563). Overall, differential changes in body mass index, body weight, and waist circumference in response to weight loss intervention were not significantly different between FTO genotypes. Sensitivity analyses indicated that differential changes in body mass index, body weight, and waist circumference by FTO genotype did not differ by intervention type, intervention length, ethnicity, sample size, sex, and baseline body mass index and age category. Conclusions  We have observed that carriage of the FTO minor allele was not associated with differential change in adiposity after weight loss interventions. These findings show that individuals carrying the minor allele respond equally well to dietary, physical activity, or drug based weight loss interventions and thus genetic predisposition to obesity associated with the FTO minor allele can be at least partly counteracted through such interventions. Systematic review registration  PROSPERO CRD42015015969.